Tendon‐derived extracellular matrix induces mesenchymal stem cell tenogenesis via an integrin/transforming growth factor‐β crosstalk‐mediated mechanism. Issue 6 (17th April 2020) - Wang, Dan; Pun, Charmaine C. M.; Huang, Shuting; Tang, Thomas C. M.; Ho, Kevin K. W.; Rothrauff, Benjamin B.; Yung, Patrick S. H.; Blocki, Anna M.; Ker, Elmer D.F.; Tuan, Rocky S.
Abstract: Treatment of tendon injuries is challenging. To develop means to augment tendon regeneration, we have previously prepared a soluble, low immunogenic (DNA‐free), tendon extracellular matrix fraction (tECM) by urea extraction of juvenile bovine tendons, which is capable of enhancing transforming growth factor‐β (TGF‐β) mediated tenogenesis in human adipose‐derived stem cells (hASCs). Here, we aimed to elucidate the mechanism of tECM‐driven hASC tenogenic differentiation in vitro, focusing on the integrin and TGF‐β/SMAD pathways. Our results showed that tECM promoted hASC proliferation and tenogenic differentiation in vitro based on tenogenesis‐associated markers. tECM also induced higher expression of several integrin subunits and TGF‐β receptors, and nuclear translocation of p‐SMAD2 in hASCs. Pharmacological inhibition of integrin‐ECM binding, focal adhesion kinase (FAK) signaling, or TGF‐β signaling independently led to compromised pro‐tenogenic effects of tECM and actin fiber polymerization. Additionally, integrin blockade inhibited tECM‐driven TGFBR2 expression, while inhibiting TGF‐β signaling decreased tECM‐mediated expression of integrin α1, α2, and β1 in hASCs. Together, these findings suggest that the strong pro‐tenogenic bioactivity of tECM is regulated via integrin/TGF‐β signaling crosstalk. Understanding how integrins interact with signaling by TGF‐β and/or other growth factors (GFs) within the tendon ECM microenvironment will provide a rational basis for an ECM‐based approach for tendon repair.